Landscape metrics selection and influence over hydrological signatures: land use change’s effect over water resources in Chile - Henriquez-Dole, Lenin Esau; Gironás, Jorge; Meza, Francisco; Salazar, Esthela; Henríquez, Cristian (Frontiers in Environmental Science, 2025)
Ecosystems are vulnerable to water scarcity and human-induced landscape tranformations. This study evaluates how land use changes alter hydrological regimes in water-scarce regions, such as drylands, employing a novel framework integrating class-level landscape metrics (LM) and Indicators of Hydrologic Alteration (IHA). Historical (1990–2017) and future land use scenarios - Business as Usual (BAU) and Strategic Land Use Planning (PROT) - for two catchments within the Maipo River Basin in Chile were analyzed using LASSO regression to identify key LM, which reflects landscape patterns influencing hydrology. Results reveal that shape and aggregation metrics, particularly urban patch size (SHAPE_MN) and agricultural dispersion (SPLIT), could evidence strong connection between landscape dynamics and hydrology, where deviation explained in critical hydrological signatures ranges from 15% to 98% in monthly flows (IHA 1), and from 25% to 99% in extreme events (IHA 2). Urbanization in Rinconada de Maipú (RM) catchment amplifies peak flows and reduces baseflow, while rural abandonment in Los Almendros catchment stabilizes baseflow (+23%) through vegetation recovery. Future scenarios illustrate context-dependent outcomes. In Los Almendros, characterized by low anthropogenic intervention, PROT scenarios mitigate hydrological degradation more effectively than BAU. However, in the highly urbanized RM catchment, PROT’s benefits are limited, requiring more actions to limit hydrological impacts. Only 64% of LM (74/116) significantly relates to hydrology in the study catchments. This approach offers a replicable tool to identify the most influential landscape metrics over hydrology in a region, streamlining actionable metrics to bridge the work of land use planners and water resources planners by integrating spatial land use configuration with water resources management.